2016
DOI: 10.1016/j.jpowsour.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Nickel hexacyanoferrate, a versatile intercalation host for divalent ions from nonaqueous electrolytes

Abstract: New energy storage chemistries based on Mg ions or Ca ions can theoretically improve both the energy density and reduce the costs of batteries. To date there has been limited progress in implementing these systems due to the challenge of finding a high voltage high capacity cathode that is compatible with an electrolyte that can plate and strip the elemental metal. In order to accelerate the discovery of such a system, model systems are needed that alleviate some of the issues of incompatibility. This report d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 30 publications
(35 reference statements)
0
65
0
Order By: Relevance
“…PB analogs are an example of Metal Organic Framework structures and have been investigated widely recently as insertion electrodes for batteries . These materials have the general formula A x MFe(CN) 6 .…”
Section: Cathodes For Calcium‐ion Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…PB analogs are an example of Metal Organic Framework structures and have been investigated widely recently as insertion electrodes for batteries . These materials have the general formula A x MFe(CN) 6 .…”
Section: Cathodes For Calcium‐ion Batteriesmentioning
confidence: 99%
“…In a follow‐up study with nickel hexacyanoferrate Lipson et al[57a] found that this material could also reversibly intercalate Ca‐ions electrochemically from nonaqueous electrolytes although the initial capacity was only 60 mAh g −1 at a voltage of 2.6 V versus Ca/Ca 2+ and capacity retention with cycling was poor. These capacities are still too low for practical battery applications.…”
Section: Cathodes For Calcium‐ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The net effect is an overlapping for the electron clouds of the involved metals (M, T). This explains the attractive properties of this family of materials as prototype of molecular magnets, which have been widely studied in the last decades The presence of two redox centers linked through the CN bridge and for some compositions also of an exchangeable alkali metal (A), has stimulated their study as materials for new generation of batteries, in electrochemical sensors, environmental remediation,, and for health care . For certain combinations of metals, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…in both aqueous and non-aqueous electrolytes. [6][7][8][9][10][11][12][13][14][15] For example, Na2Fe[Fe(CN)6]·0.1H2O as a positive electrode material for non-aqueous Na-ion batteries exhibits a large specific capacity of 155 mAh/g at the average potential of 3.1 V vs. Na/Na + . 16 However, the reaction mechanism of the PBA electrodes have not been fully understood yet.…”
mentioning
confidence: 99%